Menyontek atau Tidak Menyontek: Menggali Persepsi dan Meningkatkan Efikasi Diri Siswa - Upadani, Ni Kadek Sri Reta; Swari, Made Ardha Nare; Devi, Ni Made Mirah Artati; Putri, M Ni Komang Ayu Meita; Cahyadewi, Ni Ketut Cory (Universitas Muhammadiyah Magelang, 2024)
Cheating behavior is a form of academic dishonesty to gain an advantage. The phenomenon of cheating behavior is also found at SD Saraswati 1 Denpasar, which often occurs during exams. Cheating behavior arises due to students' lack of trust and confidence in their abilities, so they choose to use the wrong method by cheating to get satisfactory grades. This is related to student self-efficacy. The intervention activity aims to build perceptions and increase student self-efficacy to minimize cheating behavior among students at SD Saraswati 1 Denpasar. The subjects in this intervention were students in class V C of SD Saraswati 1 Denpasar with a total of 29 students. Intervention activities consist of psychoeducation and play therapy in the form of role-play and playing the Wheel of Destiny. The analysis technique uses Paired Sample t-tests and observation techniques. Based on the results of the Paired Sample T-Test, it shows a significant value of 0.000 (p < 0.05), which shows that there is a difference between self-efficacy scores before and after the intervention. Observation results show that increasing students' levels of self-efficacy has an impact on reducing students' cheating behavior. There were no students who brought small notes and found answers during the exam, there were only 1–2 students who were still seen sharing answers during the exam.